2000
DOI: 10.1088/0268-1242/15/6/302
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence studies of InGaN/GaN multi-quantum wells

Abstract: We report measurements of photoluminescence, photoluminescence excitation spectroscopy and photoluminescence time decay on three MOVPE-grown InGaN/GaN multiple quantum well structures with 13% In in the wells and well widths L z = 1.25, 2.5 and 5.0 nm. The PL spectra are dominated by single emission peaks, together with phonon sidebands spaced by a GaN LO phonon energy (92 meV). The peak energies are red-shifted with respect to energies calculated for exciton recombination in square quantum wells and the wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 37 publications
8
53
0
Order By: Relevance
“…The samples were excited using the frequency tripled output of a 100 fs mode locked Ti:sapphire laser, with a photon energy of 4.881 eV. The use of a pulsed laser, with a pulse duration much shorter than the carrier recombination lifetimes for both samples, 2,8,34 ensures that the peak carrier concentration in the QWs is determined by the power density of the excitation source. This assumes that the light is mainly absorbed due to the excitation of carriers in the GaN and that these carriers are captured by the QWs.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were excited using the frequency tripled output of a 100 fs mode locked Ti:sapphire laser, with a photon energy of 4.881 eV. The use of a pulsed laser, with a pulse duration much shorter than the carrier recombination lifetimes for both samples, 2,8,34 ensures that the peak carrier concentration in the QWs is determined by the power density of the excitation source. This assumes that the light is mainly absorbed due to the excitation of carriers in the GaN and that these carriers are captured by the QWs.…”
Section: à2mentioning
confidence: 99%
“…1 Initially, it was suggested that the main advantage of non-polar InGaN/GaN QWs over their polar counterparts would be enhanced recombination efficiency due to the much shorter radiative lifetimes 2,3 compared to equivalent c-plane structures. [4][5][6][7][8] Recently, it has also been suggested that the phenomena of efficiency droop could also be influenced by the polarity of the QW structure. Efficiency droop, the reduction in the efficiency of light emitting diodes at high drive currents, is one of the most serious problems in the use of nitride Light emitting diodes (LEDs) for high brightness applications.…”
mentioning
confidence: 99%
“…We therefore use the time (s e ) required for the PL intensity to decay by a factor of 1=e from the maximum intensity to characterise each decay transient. The low temperature PL decay times of InGaN/GaN QWs are also reported 28,30,[41][42][43][44] to vary at different detection energies across the zero phonon line, with an increase in decay time as the detection energy is reduced. This effect has been explained as follows: as the detection energy is reduced, we detect carriers that are localised in regions of progressively increasing In fraction where the local built-in electric field is stronger, thus leading to a reduction in electron-hole wavefunction overlap.…”
Section: -4mentioning
confidence: 92%
“…This effect has been explained as follows: as the detection energy is reduced, we detect carriers that are localised in regions of progressively increasing In fraction where the local built-in electric field is stronger, thus leading to a reduction in electron-hole wavefunction overlap. 30,41,44 Time-integrated PL spectra and extracted PL decay times, s e , measured at different energies across the spectra as a function of temperature are shown in Fig. 5 for sample A and Fig.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation